Diversity of Surface Fibril Patterns in Mimivirus Isolates - de Aquino, Isabella Luiza Martins; Serafim, Mateus Sá Magalhães; Machado, Talita Bastos; Azevedo, Bruna Luiza; Cunha, Denilson Eduardo Silva; Ullmann, Leila Sabrina [UNESP]; Araújo, João Pessoa [UNESP]; Abrahão, Jônatas Santos (American Society for Microbiology, 2023)
Among the most intriguing structural features in the known virosphere are mimivirus surface fibrils, proteinaceous filaments approximately 150 nm long, covering the mimivirus capsid surface. Fibrils are important to promote particle adhesion to host cells, triggering phagocytosis and cell infection. However, although mimiviruses are one of the most abundant viral entities in a plethora of biomes worldwide, there has been no comparative analysis on fibril organization and abundance among distinct mimivirus isolates. Here, we describe the isolation and characterization of Megavirus caiporensis, a novel lineage C mimivirus with surface fibrils organized as “clumps.” This intriguing feature led us to expand our analyses to other mimivirus isolates. By employing a combined approach including electron microscopy, image processing, genomic sequencing, and viral prospection, we obtained evidence of at least three main patterns of surface fibrils that can be found in mimiviruses: (i) isolates containing particles with abundant fibrils, distributed homogeneously on the capsid surface; (ii) isolates with particles almost fibrilless; and (iii) isolates with particles containing fibrils in abundance, but organized as clumps, as observed in Megavirus caiporensis. A total of 15 mimivirus isolates were analyzed by microscopy, and their DNA polymerase subunit B genes were sequenced for phylogenetic analysis. We observed a unique match between evolutionarily-related viruses and their fibril profiles. Biological assays suggested that patterns of fibrils can influence viral entry in host cells. Our data contribute to the knowledge of mimivirus fibril organization and abundance, as well as raising questions on the evolution of those intriguing structures.
Keywords: amoeba; cell adhesion; diversity; fibrils; mimivirus; structural biology; virus entry